2017
DOI: 10.1002/chem.201705036
|View full text |Cite
|
Sign up to set email alerts
|

Rh‐Catalyzed Denitrogenative Reaction of N‐Sulfonyl‐1,2,3‐triazoles with Isatoic Anhydrides and Oxadiazolones

Abstract: A convenient and simple, Rh -catalyzed denitrogenative method for the synthesis of biologically interesting 2-amino-benzoxazinones and 5-amino-oxadiazoles from readily available isatoic anhydrides and oxadiazolones has been developed. These reactions proceed via an O-H insertion onto α-imino Rh -carbenoid species followed by a rearrangement. The scope of the reaction can also be extended to benzoxazinones to access amino-substituted benzoxazines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…Recently, Fokin demonstrated that the sterically hindered secondary amides could undergo selective conversion through an O–H insertion followed by a rearrangement to deliver α-amine ketones (Scheme a) . Another secondary amide activation process that relies on the tautomerism of 2-arylquinazolinone analogues has been achieved by several groups (Scheme b) . In addition, Deng and Volla independently reported a rhodium-catalyzed transformation of activated secondary amides with 1-sulfonyl-1,2,3-triazoles (Scheme c) .…”
mentioning
confidence: 99%
“…Recently, Fokin demonstrated that the sterically hindered secondary amides could undergo selective conversion through an O–H insertion followed by a rearrangement to deliver α-amine ketones (Scheme a) . Another secondary amide activation process that relies on the tautomerism of 2-arylquinazolinone analogues has been achieved by several groups (Scheme b) . In addition, Deng and Volla independently reported a rhodium-catalyzed transformation of activated secondary amides with 1-sulfonyl-1,2,3-triazoles (Scheme c) .…”
mentioning
confidence: 99%
“…[55] In the next year, another denitrogenative strategy for the effective synthesis of 2-amino-benzoxazinones 170 was developed by our group from easily available isatoic anhydrides 166 and N-sulfonyl-1,2,3-triazoles 9 (Scheme 37). [56] The reaction followed a Rh(II)-catalyzed tandem OÀ H insertion onto highly reactive Rh-azavinyl carbenes and subsequent intramolecular rearrangement to produce highly substituted 2- Along the same lines, in 2019, we revealed a Rh(II)catalyzed highly diastereoselective methodology for the efficient synthesis of structurally diverse tricyclic 2-imidazolones 176 by reacting 4-vinyl benzoxazinanones 175 with Nsulfonyl-1,2,3-triazoles 9 under operationally simple conditions (Scheme 38). [57] The reaction mechanism was proposed to proceed via a highly selective OÀ H insertion of RhÀ AVC followed by intramolecular rearrangement and cyclization process and involved the sequential formation of four new bonds (two CÀ N and two CÀ O bonds) in a cascade fashion (Scheme 39).…”
Section: Oà H Nà H Insertionmentioning
confidence: 99%
“…Rhodium-stabilized donor/acceptor carbenes as reactive intermediates have been widely applied in modern organic synthesis [14][15][16][17][18][19][20][21][22][23][24][25][26]. Among them, N-sulfonyl-1,2,3-triazole as an alternative source of carbene precursor has been used to achieve the transannulation reaction for the direct synthesis of heterocycles [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%